2010
DOI: 10.1086/651080
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Non‐typhoid Salmonellae Establish Systemic Intracellular Infection in HIV‐Infected Adults: An Emerging Disease Pathogenesis

Abstract: Invasive NTS have established a new and emerging pathogenesis in the context of HIV infection in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 40 publications
(32 reference statements)
2
80
0
1
Order By: Relevance
“…A prospective study of the concentration of S. Typhi in blood of typhoid fever patients showed a median value of 0.3 (range of 0.1 to 399) CFU/ml, well below current PCR-based detection limits [16]. Gordon et al [2] have shown that NTS in bacteremic patients are present at a similarly low concentration (1 CFU/ml).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A prospective study of the concentration of S. Typhi in blood of typhoid fever patients showed a median value of 0.3 (range of 0.1 to 399) CFU/ml, well below current PCR-based detection limits [16]. Gordon et al [2] have shown that NTS in bacteremic patients are present at a similarly low concentration (1 CFU/ml).…”
Section: Discussionmentioning
confidence: 90%
“…Salmonella enterica serovar Typhi is exclusively host-restricted to humans, and early intracellular replication within reticuloendothelial mononuclear cells is critical for pathogenesis [1]. In contrast, non-typhoid Salmonella (NTS) serovars have a broad host range and usually cause self-limiting mucosal diarrheal disease and carriage in immunocompetent humans [2].…”
Section: Introductionmentioning
confidence: 99%
“…Gordon and colleagues 16 asserted that counts of S. typhi in blood of patients with typhoid fever mostly indicate a median concentration of one bacterium per millilitre during the first and second weeks of the illness. Thus, S. typhi is most frequently isolated during this time.…”
Section: Resultsmentioning
confidence: 99%
“…For culture-based and molecular diagnostics, similar challenges present with typhoidal Salmonella-low bacterial burden (1CFU/ml) in blood-may confound sensitive diagnosis of NTS [152]. PCR assays have been clinically validated for diagnosis of enterocolitis or for use on cultured isolates, but not for direct diagnosis of invasive infections [153,154].…”
Section: Available Diagnostic Approaches For Ntsmentioning
confidence: 99%